A Conceptual Design of Infrastructures and Facilities in Distribution Center for Frozen and Chilled Fishery Products - C. Boonmee (2020)
© 2019 IEEE. This study aims to propose a conceptual design of infrastructures and facilities in the distribution center for frozen and chilled fishery products connecting lower northern provinces to the nearby countries. Firstly, several data were collected and analyzed including primary data and secondary data. Secondly, the activities were listed based on primary data and secondary data. Thirdly, the infrastructures and facilities are proposed that were listed from the activity analysis. Finally, the conceptual design was proposed for designing the infrastructures and facilities in the distribution center for frozen and chilled fishery products. The general function of infrastructures and facilities in the distribution center was firstly proposed. Then, the additional functions that might be integrated were proposed in which the additional functions consisted of retail function, light industrial function, and custom function. This study presented not only possible activities but also infrastructures and facilities in the distribution center for frozen and chilled fishery products to connect lower northern provinces to the nearby countries in which this lead to the development of the economic growth in Thailand and neighboring countries as well.